2022
DOI: 10.3390/cancers14235803
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Lymphadenectomy May Not Improve Biochemical Recurrence-Free Survival in Patients with Prostate Cancer Treated with Robot-Assisted Radical Prostatectomy in Japan (The MSUG94 Group)

Abstract: In this multicenter retrospective cohort study, we aimed to evaluate whether pelvic lymph node dissection (PLND) improved biochemical recurrence (BCR) in patients with prostate cancer (PCa) who underwent robot-assisted radical prostatectomy (RARP) in Japan. A multicenter retrospective cohort study of 3195 PCa patients undergoing RARP at nine institutions in Japan was conducted. Enrolled patients were divided into two groups: those who underwent RARP without PLND (non-PLND group) and those who underwent PLND (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Multivariate Cox regression analysis showed that treatment with RT + ADT significantly reduced the risk of BCR compared to RP (hazard ratio [HR] 0.162, p < 0.001). However, there was no significant difference in the risk of local recurrence, distant metastasis, or OS between the two treatment modalities ( p = 0.470, p = 0.268, p = 0.509, respectively) [ 28 ]. Therefore, it is necessary to determine which treatment should be chosen for high-risk PCa when considering OS as an endpoint.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Multivariate Cox regression analysis showed that treatment with RT + ADT significantly reduced the risk of BCR compared to RP (hazard ratio [HR] 0.162, p < 0.001). However, there was no significant difference in the risk of local recurrence, distant metastasis, or OS between the two treatment modalities ( p = 0.470, p = 0.268, p = 0.509, respectively) [ 28 ]. Therefore, it is necessary to determine which treatment should be chosen for high-risk PCa when considering OS as an endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in which PLND was associated with an improved BCR, a 2-year BRFS rate of 93% was reported in 439 patients who underwent RARP with PLND, although the median follow-up period was only 16 months [ 43 ]. According to a multicenter retrospective cohort study of 3195 patients with PCa who underwent RARP at nine institutions in Japan, the 2-year BRFS rates were 95.8% in patients who underwent RARP without PLND and 94.3% in those with PLND ( p = 0.855) [ 28 ]. In this study, the BRFS rate in the ADT + UFT group was also similar to that in the non-high-risk PCa group and the RARP + PLND group [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to various guidelines, ePLND is strongly recommended as a surgical treatment for high-risk PCa [3,4]. However, there is currently disagreement as to whether pelvic lymph node dissection (PLND) should be performed in any patient when performing RP for PCa [34]. The benefits of ePLND include improved accuracy in precisely staging PCa [30].…”
Section: Extended Pelvic Lymph Node Dissection For High-risk Pcamentioning
confidence: 99%